Effect of Huaier granule on prognosis of breast cancer: A single-center propensity score matching retrospective study - Qianqian Guo; Yuting Peng; Ge Zhang; Huan Lin; Qianjun Chen; Sihan Zhou; Xiuyuan Hao (Chinese Medical Journal)
Abstract. Background:. Huaier granule is an important medicinal fungus extract widely used in cancer treatment. Previous retrospective studies have reported its effectiveness in breast cancer patients, but the imbalanced baseline characteristics of participants could have biased the results. Therefore, this retrospective study aimed to examine the efficacy of Huaier granule on the prognosis of breast cancer patients. Methods:. In this single-center cohort study, breast cancer patients diagnosed and treated at the Guangdong Provincial Hospital of Chinese Medicine between 2009 and 2017 were selected. The data were retrospectively analyzed and divided into two groups according to whether the patients received Huaier granules. The propensity score matching (PSM) method was used to eliminate selection bias. The disease-free survival (DFS) and overall survival (OS) for these groups were compared using the Kaplan–Meier method and the Cox regression. Results:. This study included 214 early invasive breast cancer patients, 107 in the Huaier group and 107 in the control group. In the Kaplan–Meier analysis, the 2-year and 5-year DFS rates were significantly different in the Huaier group and control group (hazard ratio [HR], 0.495; 95% confidence interval [CI], 0.257–0.953; P = 0.023). The 2-year and 5-year OS rates were also significantly different (HR, 0.308; 95% CI, 0.148–0.644; P = 0.001). On multivariable Cox regression, Huaier granule was associated with improved DFS (HR, 0.440; 95% CI, 0.223–0.868; P = 0.018) and OS (HR, 0.236; 95% CI, 0.103–0.540; P = 0.001). Conclusion:. In this retrospective study, Huaier granules improved the DFS and OS of early invasive breast cancer patients, providing real-world evidence for further prospective studies on treating breast cancer with Huaier granules.